Sharia-Based Retail Business Development Strategy in Enhancing the Economic Independence of Islamic Boarding Schools in North Lombok Regency Strategi - Dian Aulia Mutia Sari; Muhammad Mahfuz (Business Management, 2026)
This study aims to analyze the development strategy of sharia-based retail business and its impact on enhancing the economic independence of Islamic boarding schools (pesantren) in North Lombok Regency. Amid modern economic challenges, pesantren are required not only to carry out religious education functions but also to establish a strong independent financial foundation. This descriptive qualitative study focuses on entrepreneurial pesantren in North Lombok Regency, including Al-Istiqomah Islamic Boarding School in Sama Guna Village. Data were collected through in-depth interviews, participatory observation, and documentation analysis. The results indicate that the strategy for developing sharia retail units (such as pesantren marts and cooperatives) is implemented through modern management practices (POAC), sharia operational standards (Clean, Display, Fair Pricing, Ethical Promotion, Strategic Location), and the 5C+1S evaluation system. The transformation of sharia retail businesses significantly strengthens pesantren financial autonomy and fosters students' digital entrepreneurial skills.